How exercise adherence affects emotion regulation in Chinese college students: The chain mediating effect of sleep quality and self-efficacy - Guowei Wang; Zeyuan Wang; Fanzheng Mu; Guolin Li; Bo Li (PLoS ONE, 2026)
Objective This study investigated the mechanism through which exercise adherence enhances emotional regulation ability in college students, focusing on the chain mediating pathway involving sleep quality and self-efficacy. It provides a theoretical foundation for exercise-based interventions to promote psychological health in this population. Methods A cross-sectional design was employed, with 8,899 chinese college students from Henan Province selected via stratified cluster sampling. Data were collected using the Exercise Adherence Scale (EAS), Emotional Intelligence Scale (EIS), Pittsburgh Sleep Quality Index (PSQI), and General Self-Efficacy Scale (GSES). Statistical analyses were conducted using EXCEL, Mplus 8.3, and SPSS 27.0.1. Results Exercise adherence exerted a significant direct positive effect on emotional regulation (β = 0.289,56.67% of the total effect) . Significant independent mediating effects were observed for sleep quality (β = 0.010,6.33%) and self-efficacy (β = 0.200,89.59%) . Crucially, a chain mediation pathway was identified: exercise adherence improved sleep quality, which subsequently enhanced self-efficacy, ultimately strengthening emotional regulation ability (β = 0.010,4.52%) . Conclusion Exercise adherence directly enhances emotional regulation and indirectly influences it through the “sleep quality → self-efficacy” chain pathway. These findings reveal a synergistic multi-path mechanism and provide empirical support for designing targeted exercise-based mental health interventions.